Concentration in Academic Publishing and Journal Impact: A Descriptive Assessment of Top 46 Business Journals - Zavadskiy, Gleb; Guru Muniasamy, Ilango; Mithas, Sunil (Production and Operations Management, 2026)
This study assesses concentration of the top 50 universities (T50 concentration) in premier business journals and its correlation with journal impact metrics. We use 2008–2022 data from the Web of Science and Clarivate Analytics, focusing on 46 business journals from the University of Texas at Dallas (UTD 24) and Financial Times (FT 50) lists to document several findings. First, we find that the top 50 institutions, representing less than 0.5% of business schools globally, contribute a disproportionately large share of about 53% publications in these outlets. Second, our longitudinal analyses indicate that T50 concentration has remained relatively stable over the 15-year period. Finally, we find evidence of a positive and statistically significant association between T50 concentration and Article Influence Score, although we do not find any statistically significant relationship with other journal impact metrics. Importantly, we find a decline in the publication and citation share of articles authored exclusively by top-50 author teams, and a rise in share for mixed author teams from top-50 and non-top-50 universities. These findings provide data-driven insights to inform debates relating to merit and elitism in editorial and review processes in top journals.